2023
DOI: 10.1128/msystems.01300-22
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Probio-X Treatment Enhances the Therapeutic Effect of a Conventional Drug in Managing Type 2 Diabetes Mellitus by Promoting Short-Chain Fatty Acid-Producing Bacteria and Bile Acid Pathways

Abstract: Metformin causes variable adverse gastrointestinal effects, especially after prolonged treatment. We found that cotreatment with Probio-X and metformin for the management of type 2 diabetes mellitus may promote gut SCFA-producing bacteria and the levels of specific bile acids, thus increasing the secretion of related gastrointestinal hormones and ultimately improving glucose homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Diet-host-fecal microbiota interactions exist, and this relationship was also evident in the network analysis in this paper. Diets modify the body condition of dogs through their effect on body metabolism and act as a link between the host and the gut microbiota through secondary bile acids [109,110]. This suggests that further research is needed on the mechanism by which diet energy levels affect canine metabolism, and it suggests that attention should be paid to the role of fecal metabolites as biomarkers in pet food development to better monitor food-pet interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Diet-host-fecal microbiota interactions exist, and this relationship was also evident in the network analysis in this paper. Diets modify the body condition of dogs through their effect on body metabolism and act as a link between the host and the gut microbiota through secondary bile acids [109,110]. This suggests that further research is needed on the mechanism by which diet energy levels affect canine metabolism, and it suggests that attention should be paid to the role of fecal metabolites as biomarkers in pet food development to better monitor food-pet interactions.…”
Section: Discussionmentioning
confidence: 99%
“…By colonizing the gut microbiota or supplementing with probiotics, insulin resistance, body mass index, and gut microbiota composition in T2DM patients can be significantly improved ( 140 , 141 ). A randomized, double-blind, placebo-controlled trial found that a combination probiotic, Probio-X (composed of Lactobacillus casei LCZ, Lactobacillus plantarum P-8, Lactobacillus rhamnosus Probio-M9, Lactobacillus paracasei Probio-M8 , and Lactobacillus paracasei V9 ), can enhance the therapeutic effect of metformin in T2DM by promoting the production of short-chain fatty acids and the bile acid pathway ( 142 ). Adding the gut commensal bacterium Alistipes onderdonkii to diet-induced obese mice can also reduce hyperglycemia, alleviate inflammation and glucose intolerance induced by high fat ( 143 ).…”
Section: Dysbiosis Of the Gut Microbiota Can Lead To Metabolic Disordersmentioning
confidence: 99%
“…11 A clinical trial demonstrated that coadministration of probiotics and metformin can improve the symptoms of T2D patients by enhancing the secretion of short-chain fatty acids and bile acids. 12 Probiotics have been proven to alleviate the symptoms of T2D by regulating the gut microbiota. Probiotics, particularly Lactobacillus (which are commensal inhabitants of the human gastrointestinal tract and commercially prepared as probiotics to restore the normal microbiota after imbalance created by antibiotic therapy), have been shown to be the prospective biotherapeutics for T2D in in vitro and in vivo animal models.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Probiotics, as a part of the gut microbiota, have received increasing attention in preventing and treating T2D . A clinical trial demonstrated that coadministration of probiotics and metformin can improve the symptoms of T2D patients by enhancing the secretion of short-chain fatty acids and bile acids . Probiotics have been proven to alleviate the symptoms of T2D by regulating the gut microbiota.…”
Section: Introductionmentioning
confidence: 99%